Mallard survival and nesting ecology in the Lower Great Lakes Region, New York - Matthew R. Kaminski; Guy A. Baldassarre; J. Brian Davis; Eric R. Wengert; Richard M. Kaminski (Wildlife Society Bulletin)
ABSTRACT Ecology of mallards (Anas platyrhynchos) breeding in the Lower Great Lakes Region of the United States has not been investigated as comprehensively as mid‐continent populations of this species. We studied mallard breeding ecology in the Cowaselon Creek Watershed Area in New York during 2003–2004. Daily and 100‐day breeding season survival of female mallards (n = 41) was 0.997 and 0.782, respectively, and was positively influenced by female age and body mass at time of capture. Eight radiomarked female mallards were killed by either mammalian or avian predators. Earliest and latest nest initiation dates were 14 April and 24 May 2003–2004, respectively, and females initiated nests in wetlands 10 days earlier than in uplands. Overall, average clutch size was 9.4 ± 0.32 eggs (SE), and probability of reproductive success of females was 0.27, with nest success in wetlands and uplands of 0.71 and 0.42, respectively. Daily and 35‐day nest success was 0.968 and 0.326, respectively. We found an estimated 70% of all initiated nests prior to clutch destruction or hatch; thus, our estimates of nesting and re‐nesting effort may be biased low. Survival of breeding females and nest success were comparable or exceeded parameter estimates from other regions of the mallard breeding range. We suggest that wetland and upland habitats are both important to nesting mallards in New York and elsewhere in the Lower Great Lakes Region. © 2013 The Wildlife Society.